O zmianach zielonogórskich urbanonimów spowodowanych względami politycznymi (z perspektywy dyskursu publicznego) = About changes of Zielona Góra urbanonyms caused by political reasons (from the perspective of public discourse) - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of reflection in this article are the causes and course of changes in post-war urbanonyms of Zielona Góra (especially due to political considerations) from the perspective of public discourse. The analysis of the various participants in this discourse, i.e. politicians, journalists and ordinary citizens, has been analyzed. The names themselves were also taken into account, testifying about the people who gave them, their views, convictions, motives they were guided by.
Keywords: dyskurs; urbanonimy; zmiany w nazewnictwie; argumentacja; discourse; urbanonyms; changes in names; argumentation